Case report: Novel genotype of ALG2-CDG and confirmation of the heptasaccharide glycan (NeuAc-Gal-GlcNAc-Man2-GlcNAc2) as a specific diagnostic biomarker - Martínez Duncker, Ivan; Mata-Salgado, Denisse; Shammas, Ibrahim; Ranatunga, Wasantha; Daniel, Earnest James Paul; Cruz Muñoz, Mario E.; Abreu, Melania; Mora-Montes, Héctor; He, Miao; Morava, Eva; Zafra de la Rosa, Gildardo (Frontiers in Genetics, 2024)
This report outlines the case of a child affected by a type of congenital disorder of glycosylation (CDG) known as ALG2-CDG (OMIM 607906), presenting as a congenital myasthenic syndrome (CMS) caused by variants identified in ALG2, which encodes an α1,3mannosyltransferase (EC 2.4.1.132) involved in the early steps of N-glycosylation. To date, fourteen cases of ALG2-CDG have been documented worldwide. From birth, the child experienced perinatal asphyxia, muscular weakness, feeding difficulties linked to an absence of the sucking reflex, congenital hip dislocation, and hypotonia. Over time, additional complications emerged, such as inspiratory stridor, gastroesophageal reflux, low intake, recurrent seizures, respiratory infections, an inability to maintain the head upright, and a global developmental delay. Whole genome sequencing (WGS) revealed the presence of two ALG2 variants in compound heterozygosity: a novel variant c.1055_1056delinsTGA p.(Ser352Leufs*3) and a variant of uncertain significance (VUS) c.964C>A p.(Pro322Thr).Additional studies, including determination of carbohydrate-deficient transferrin (CDT) revealed a mild type I CDG pattern and the presence of an abnormal transferrin glycoform containing a linear heptasaccharide consisting of one sialic acid, one galactose, one N-acetylglucosamine, two mannoses and two N-acetylglucosamines (NeuAc-Gal-GlcNAc-Man2-GlcNAc2), ALG2-CDG diagnostic biomarker, confirming the pathogenicity of these variants.